2012
DOI: 10.1166/rnn.2012.1014
|View full text |Cite
|
Sign up to set email alerts
|

Computational Modeling of Nanoparticle Targeted Drug Delivery

Abstract: Nanomedicine is a promising application of nanotechnology in medicine, which can drastically improve drug delivery efficiency through targeted delivery. However, characterization of the nanoparticle targeted delivery process under vascular environment is very challenging due to the small scale of nanoparticles and the complex in vivo vascular system. To understand such complicated system, various computational models are developed to help reveal nanoparticle targeted delivery process and design nanoparticles f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
52
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(52 citation statements)
references
References 72 publications
0
52
0
Order By: Relevance
“…Theoretical work by Decuzzi and Ferrari et al concluded that rod-shaped particles have higher adhesion/contact probability than spherical particles [63]. Further results from a computational model created by Liu et al, showed an increase in binding probability with increasing aspect ratio [64,65]. Confirming these theoretical finds, Mitragotri reported that rod-shaped particles exhibit higher avidity and selectivity toward their target than their spherical counterparts in vivo [66].…”
Section: Surface Functionalization For Passive and Active Targetingmentioning
confidence: 86%
“…Theoretical work by Decuzzi and Ferrari et al concluded that rod-shaped particles have higher adhesion/contact probability than spherical particles [63]. Further results from a computational model created by Liu et al, showed an increase in binding probability with increasing aspect ratio [64,65]. Confirming these theoretical finds, Mitragotri reported that rod-shaped particles exhibit higher avidity and selectivity toward their target than their spherical counterparts in vivo [66].…”
Section: Surface Functionalization For Passive and Active Targetingmentioning
confidence: 86%
“…This approach assumes small nanodrug loading, one-way fluid-particle coupling, and negligible nanodrug coagulation. Multiple studies have used this computational approach for modeling nanoparticle transport in vascular systems [33][34][35][36]. The diffusion of NPs in blood flow can be due to (1) Brownian diffusion caused by the bombardment of fluid molecules and (2) shear-induced diffusion due to the presence of red blood cells (RBCs) in shear flow.…”
Section: Computational Modelsmentioning
confidence: 99%
“…Additionally, more sophisticated models exist which include drug release and ligand-receptor binding [36,42]. For instance, in Haun and Hammer [42], a rate equation was used to model the kinetics of nanoparticle adhesion via ligand-receptor binding:…”
Section: Computational Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the other hand, the targeted delivery poses difficulty due to the small scale of nanoparticles and the complex in vivo vascular system. However, to understand 11 The nanoparticles studied in anticancer medicine comprise various lipids and natural or synthetic polymers. Among various biodegradable polymers, one of the most preferred for controlled release is polylactic acidco-glycolic acid (PLGA).…”
Section: Introductionmentioning
confidence: 99%